Understanding polyspecificity of multidrug ABC transporters: closing in on the gaps in ABCB1 - Gutmann, Daniel A. P. (Trends Biochem Sci, 2009)
Multidrug ABC transporters can transport a wide range of drugs from the cell. Ongoing studies of the prototype mammalian multidrug resistance ATP-binding cassette transporter P-glycoprotein (ABCB1) have revealed many intriguing functional and biochemical features. However, a gap remains in our knowledge regarding the molecular basis of its broad specificity for structurally unrelated ligands. Recently, the first crystal structures of ligand-free and ligand-bound ABCB1 showed ligand binding in a cavity between its two membrane domains, and now previous observations on polyspecificity can be interpreted in a structural context. The new ABCB1 crystal structures also suggest a critical role for an axial rotation of transmembrane helices for high-affinity binding and low-affinity release of ligands during transmembrane transport.